The Use of Modified Templates in Early and Advanced Stage Nonseminomatous Germ Cell Tumor. (5th April 2018) - Masterson, Timothy A.; Cary, Clint
Abstract : The surgical management of both early and advanced stage germ cell tumors of the testis remains a complex process of surgical decision making to maximize oncologic control while minimizing morbidity. Over the past 5 decades, the evolution of the surgical template for retroperitoneal lymphadenectomy (RPLND) has resulted in important modifications to achieve these goals. In this review, we will characterize the historical motivating factors that led to the modified template, outline patient and clinical factors in selecting these approaches in both early and advanced stage disease, and briefly discuss future horizons for their implementation.